JENIS KUPU - KUPU DI DESA SAHULAU KECAMATAN TELUK ELPAPUTIH KABUPATEN MALUKU TENGAH - Lesly Latupapua; J. F. Sahusilawane; D. Joktery (Jurnal Hutan Tropis, 2021)
This study aims to determine the types of butterflies in Sahulau Village, Teluk Elpaputih District, Central Maluku Regency. To achieve these objectives, the method used, namely the variable circular plot (VCP) method, observations are made at each point made in each path. The distance between the center point of one plot with another plot is 150 m with a radius of 50 with a length of track that is adjusted to the study location. Catching butterflies was carried out on the entire area of the observation circle and recorded all species found, the butterflies were captured using a net then the captured butterflies were wrapped in papilot paper and placed in a specimen box before identification. The results showed that there were 28 species of butterflies spread over 5 families, namely, Papilionidae, Nymphalidae, Peridae, Lycanidae and Hespiridae, with a total of 107 individuals. Dominant types were from the family Nymphalidae with a percentage of 39%, Papilionidae 29%, Peridae 21 %, 7% Hespiriidae and the least found family is Lycanidae with a percentage of 4%. From the results of data analysis, the diversity index of 3,191 (H ') and the species wealth index of 5,778 (D) were classified as high, while the Domination Index of 0.046 (C) was classified as low.